2016
DOI: 10.2131/jts.41.17
|View full text |Cite
|
Sign up to set email alerts
|

Acute pulmonary toxicity and inflammation induced by combined exposure to didecyldimethylammonium chloride and ethylene glycol in rats

Abstract: Didecyldimethylammonium chloride (DDAC), an antimicrobial agent, has been reported to induce pulmonary toxicity in animal studies. DDAC is frequently used in spray-form household products in combination with ethylene glycol (EG). The purpose of this study was to evaluate the toxic interaction between DDAC and EG in the lung. DDAC at a sub-toxic dose (100 μg/kg body weight) was mixed with a non-toxic dose of EG (100 or 200 μg/kg body weight), and was administrated to rats via intratracheal instillation. Lactate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 31 publications
1
12
1
Order By: Relevance
“…This suggests that a non-sensitizing excipient such as EG could lessen the SS potency of an ingredient that actively sensitizes the skin. However, contrary to this result, other in vivo (Kwon et al, 2016) and in vitro (Kwon et al, 2015) studies showed that EG further potentiates the ability of DDAC to induce pulmonary toxicity. It is possible that this disparity reflects the different cell lines that were used, namely, the THP-1 human monocytic leukemia cell line versus the BEAS-2B normal human bronchial epithelial cell line.…”
Section: Discussioncontrasting
confidence: 78%
“…This suggests that a non-sensitizing excipient such as EG could lessen the SS potency of an ingredient that actively sensitizes the skin. However, contrary to this result, other in vivo (Kwon et al, 2016) and in vitro (Kwon et al, 2015) studies showed that EG further potentiates the ability of DDAC to induce pulmonary toxicity. It is possible that this disparity reflects the different cell lines that were used, namely, the THP-1 human monocytic leukemia cell line versus the BEAS-2B normal human bronchial epithelial cell line.…”
Section: Discussioncontrasting
confidence: 78%
“…DDAC‐induced cytotoxicity is potentiated in the presence of nontoxic doses of EG in human bronchial epithelial (BEAS‐2B) cells, and the effect is dependent on the concentration of EG . Moreover, rats intratracheally instilled with the mixture of DDAC and EG show significant pulmonary toxicity and inflammation, whereas the individual chemicals do not induce toxicity in respiratory organs . These findings appear to be quite similar to the results of the present study, with the same aspects of cytotoxicity induced by the combination of the QAC and organic solvent.…”
Section: Discussionsupporting
confidence: 88%
“…Besides the humidifier disinfectant, we need an exhaustive inspection on all biocide products that are distributed in Korea, especially spray products that easily expose biocide through air. Toxicological study using mice reports that ammonium chloride, which is used as a source material in deodorants, can cause pulmonary fibrosis, and a few studies confirm that didecyldimethylammonium chloride increases a number of inflammatory markers that cause pulmonary fibrosis [ 6 - 8 ]. Therefore, an exhaustive inspection is needed on all source materials used in products like disinfectants, sterilizers, preservatives, pest controls, and antifoulants distributed in Korea in order to understand the use of the products and figure out their potential risk.…”
Section: Discussionmentioning
confidence: 99%